Disclosing the Regeneration of Endek Weaving Craftsmen in Bali - Ida Ayu Oka Martini; A.A.N Eddy Supriyadinatha Gorda; A.A.N. Oka Suryadinatha Gorda; Desak Made Febri Purnama Sari (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2021)
Abstract: This study aims to investigate the regeneration of endek weaving craftsmen in Klungkung, Bali. The research method used is descriptive qualitative research. The research location is in Klungkung, Bali. The technique of collecting data through interviews was conducted on four groups of informants, namely business owners, craftsmen, children of craftsmen, and community leaders. The data analysis technique used is the interactive model of Miles and Huberman, namely: data reduction, data display, and verification. The results showed that regeneration attempts have not yet been successful due to several factors, including: 1) the younger generation’s lack of interest in weaving, 2) the number of promising job alternatives, and 3) the lack of love and pride in the younger generation for endek woven fabric products. The regeneration process functions through outreach carried out by networks of family, friends, and neighbors.Keywords: regeneration, socialization, weaving Mengungkap Regenerasi Pengrajin Tenun Endek di BaliAbstrak: Penelitian ini bertujuan untuk mengetahui regenerasi pengrajin tenun endek di Klungkung, Bali. Metode penelitian yang digunakan adalah penelitian kualitatif deskriptif. Lokasi penelitian berada di Klungkung, Bali. Teknik pengumpulan data melalui wawancara dilakukan terhadap empat kelompok informan yaitu pemilik usaha, pengrajin, anak pengrajin, dan tokoh masyarakat. Teknik analisis data yang digunakan adalah model interaktif Miles dan Huberman yaitu: reduksi data, display data, dan verifikasi. Hasil penelitian menunjukkan bahwa upaya regenerasi belum berhasil karena beberapa faktor, antara lain: 1) kurangnya minat generasi muda dalam menenun, 2) banyaknya alternatif pekerjaan yang menjanjikan, dan 3) kurangnya rasa cinta dan bangga pada yang lebih muda. generasi untuk produk kain tenun endek. Proses regenerasi berfungsi melalui sosialisasi yang dilakukan oleh jaringan keluarga, teman, dan tetangga. Kata kunci: regenerasi, sosialisasi, tenun